Analysis of The Addition of Natural Preservative Ingredients To The Saving Time of Squid (Loligo Sp.) (Study Of Various Studies Conducted) - Syauqibik, Achmad; Liviawaty, Evi; Farhansyah, Muhammad; Fauzan, Muhamad; Riyadi, Reihan Slamet (Eduvest - Journal of Universal Studies, 2023)
Squid is one of Indonesia's marine fisheries resources that is nutritious and in high demand by the public, hence the need for good quality squid. The obstacle experienced in fulfilling the demand for squid is the quality of squid. Various research have been conducted to determine preservatives that are effective enough to maintain the freshness of squid for a long time and extend the shelf life. This research was conducted using a literature study technique, comparing and selecting the most effective of several natural preservatives used. Some of the preservatives compared were lactate solution from cabbage fermentation, yogurt, chitosan solution, picung seeds, and cucumber. This study aims to determine the effective preservatives that have the longest shelf life for squid. The results of the literature study showed that yoghurt was the most effective preservative for extending the shelf life of squid until day 11 with total lactic acid bacteria colonies of 4.8x 105 cfu/gram and pH value of 6.8 in low temperature storage. The concentration used was 1.5%.